Revisiting Family Firms - Parise, Gianpaolo (Journal of Financial and Quantitative Analysis, 2024)
Abstract I propose a novel measure to identify family firms based on the number of family links between high-ranking coworkers. Leveraging this measure, I reexamine previous findings in the literature and derive four novel facts: i) Measures of stock ownership misclassify firms with a large family presence. ii) Family-run firms exhibit value stock characteristics, whereas founder-CEO firms display growth stock characteristics. iii) Family-run firms pay lower costs. iv) Family managers behave myopically. I conclude that failing to consider family links can lead to highly misleading results in the study of family firms.